PENGELOLAAN ZAKAT DALAM KEBIJAKAN SOSIAL DAN IMPLIKASINYA TERHADAP NILAI IBADAH - Nafsiatul Salviya; Rizka Ayu Sofiani; Muhammad Aditya Syah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. Zakat is one of the pillars of Islam that has spiritual, social, and economic dimensions. In contemporary developments, zakat is increasingly positioned as a social policy instrument to support poverty alleviation programs and improve community welfare. This approach, although aimed at achieving public benefit, has the potential to reduce the essence of zakat as a religious obligation if it places too much emphasis on economic utility and policy effectiveness. This article aims to analyze the management of zakat within the framework of social policy and examine its implications for the value of zakat as a religious obligation. This study uses a qualitative method with a normative approach through a literature review of the concept of zakat in Islamic jurisprudence, the principles of worship, and the public policy framework. The results of the study show that positioning zakat as a social policy instrument without considering its spiritual dimension and sharia provisions has the potential to shift the orientation of zakat from worship to merely a mechanism of social distribution. This condition can have an impact on weakening the aspect of intention, compliance with sharia principles, and blurring the fundamental differences between zakat and state fiscal instruments. This article emphasizes the importance of maintaining a balance between the social function of zakat and its essence as an act of worship, so that zakat management policies remain in line with Islamic normative values. The contribution of this research lies in strengthening the ethical and normative perspectives in the discourse on zakat management in the realm of social policy. Keywords: Zakat Management; Social Policy; Worship Value; Islamic Public Finance; Normative Ethics.